Influence of mandibular advancement on tongue dilatory movement during wakefulness and how this is related to oral appliance therapy outcome for obstructive sleep apnea. Issue 3 (21st September 2020) - Jugé, Lauriane; Yeung, Jade; Knapman, Fiona L; Burke, Peter G R; Lowth, Aimee B; Gan, Ken Z C; Brown, Elizabeth C; Butler, Jane E; Eckert, Danny J; Ngiam, Joachim; Sutherland, Kate; Cistulli, Peter A; et al.
Abstract: Study Objectives: To characterize how mandibular advancement splint (MAS) alters inspiratory tongue movement in people with obstructive sleep apnea (OSA) during wakefulness and whether this is associated with MAS treatment outcome. Methods: A total of 87 untreated OSA participants (20 women, apnea–hypopnea index (AHI) 7–102 events/h, aged 19–76 years) underwent a 3T MRI with a MAS in situ. Mid-sagittal tagged images quantified inspiratory tongue movement with the mandible in a neutral position and advanced to 70% of the maximum. Movement was quantified with harmonic phase methods. Treatment outcome was determined after at least 9 weeks of therapy. Results: A total of 72 participants completed the study: 34 were responders (AHI < 5 or AHI ≤ 10events/h with >50% reduction in AHI), 9 were partial responders (>50% reduction in AHI but AHI > 10 events/h), and 29 nonresponders (change in AHI <50% and AHI ≥ 10 events/h). About 62% (45/72) of participants had minimal inspiratory tongue movement (<1 mm) in the neutral position, and this increased to 72% (52/72) after advancing the mandible. Mandibular advancement altered inspiratory tongue movement pattern for 40% (29/72) of participants. When tongue dilatory patterns altered with advancement, 80% (4/5) of those who changed to a counterproductive movement pattern (posterior movement >1 mm) were nonresponders and 71% (5/7) of those who changed to beneficial (anterior movement >1 mm) were partial or complete responders. Conclusions: The mandibular advancement action on upper airway dilator muscles differs between individuals. When mandibular advancement alters inspiratory tongue movement, therapeutic response to MAS therapy was more common among those who convert to a beneficial movement pattern.